Перспективні напрями розвитку засобів і методів виявлення та фіксації слідів рук - Корнієнко, В.В.; Korniienko, V.V.; ORCID: http://orcid.org/0000-0002-7682-1281 (Право і безпека. – 2022. – № 4 (87). – С. 36-44, 2022)
Проведено аналіз стану дактилоскопічних дослідженьв Україні та закордоном. Приділено увагу останнім світовим досягненням у галузях хімії та мікробіології, які допомагають якісно виявляти і фіксувати сліди пальців рук людини на місці події, на різних об’єктах із подальшим проведенням досліджень у лабораторіях. Вдосконалено існуючі підходи у проявленні відбитків пальців на поверхнях(нінгідрид, алаксан, ціанакрилат, вакуумний метал VMD) та перспективні методи (наночастинки оксиду кремнію, мікробіологічні дослідження ДНК -аптамерів тощо).

Identification by fingerprints remains one of the most common ways of proving the involvement of persons in the commission of a criminal offense in law enforcement practice around the world. Over the past hundred years, the methodology of detecting and collecting fingerprints at the scene has evolved from the first attempts to use carbon black and metal powders (at the end of the 19th century) to the use of modern fluorescent powders and molecularly selective chemical compounds. The type of surface and its condition affect the choice of one or another means of finding and developing a papillary pattern. According to empirical data, difficulties arise when working with heterogeneous surfaces, leather products, granular and porous materials. Until recently, the search for prints at the scene has been negated by contamination of surfaces, as well as the presence of moisture or organic liquids. It was practically impossible to develop outdated traces, as well as to determine the approximate time of leaving the trace. The analysis of the latest foreign publications has shown significant achievements that help to effectively solve the above problems, significantly expanding the arsenal of forensic tools and methods of working with traces at the scene. Physical methods of detecting traces have received significant development. Among them, it can be singled out the use of luminescent dactyloscopic powders, which better visualize papillary patterns under UV and IR special lighting. Silicon nanoparticles with the addition of dyes, depending on the color of the surface, have shown a better result compared to the cyanoacrylate method. The scientists have managed to improve the results regarding the detection of outdated traces by combining homogeneous chemical compounds. The main ones among them are ninhydrin, which works well with dirty and wet surfaces, as well as silver nitrate and DFO solution, which reacts with organic secretions of human skin well. A vacuum deposition method (VMD) has proven to be effective, making visible prints on the surfaces of four-year-old organic plastic. The direction of immunological research of the sebaceous trace of a finger for taking samples for a DNA profile remains relevant. The presented review of foreign and domestic experience has indicated the continuation of active searches for improving methods and means of working with traces.

Проведен анализ состояния дактилоскопических исследований в Украине и за границей. Уделено внимание последним мировым достижениям в области химии и микробиологии которые помогают качественно выявлять и фиксировать следы пальцев рук человека на месте происшествия, на разных объектах с последующим проведением исследований в лабораториях. Усовершенствовано существующие подходы в проявлении отпечатков пальцев на поверхностях (нингидрид, алаксан, цианакрилат, вакуумный металл VMD) и перспективные методы (наночастицы оксида кремния, микробиологические исследования ДНК-аптамеров и т.п.).
Ospective directions for the development of means and methods for detection and fixation of handprints
Перспективные направления развития средств и методов выявления и фиксации следов рук
Корнієнко, В. В. Перспективні напрями розвитку засобів і методів виявлення та фіксації слідів рук / Василь Володимирович Корнієнко // Право і безпека. – 2022. – № 4 (87). – С. 36-44. - DOI: https://doi.org/10.32631/pb.2022.4.03.
Корнієнко В.В. Перспективні напрями розвитку засобів і методів виявлення та фіксації слідів рук. Право і безпека. 2022. No 4 (87). С. 36–44. DOI: https:// doi.org/ 10.32631/pb.2022.4.03.
Korniienko, V. V. (2022). Prospective directions for the development of means and methods for detection and fixation of handprints. Law and Safety, 4(87), 36–44. https://doi.org/ 10.32631/pb.2022.4.03.
Keywords: Криміналістика. Criminalistics. Криминалистика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; криміналістична ідентифікація; forensic identification; криминалистическая идентификация; сліди пальців людини; human fingerprints; следы пальцев человека; фіксація слідів; fixation of traces; фиксация следов; папілярні візерунки; papillary patterns; папиллярные узоры; дактилоскопія; dactyloscopy; дактилоскопия; методи і засоби пошуку та фіксації слідів